Antioxidant and physicoquemical properties evaluation of a mixed beverage during refrigerated storage - Santander-M., Margareth; Osorio M., Oswaldo; Mejía-E., Diego (Revista de Ciencias Agrícolas, 2017)
Consumers tend to buy functional foods which meet the nutritional requirements and additionally provide health benefits. The growing interest in the study of beverages with these characteristics has contributed to the development of products based on mixture of milk and fruits. The objective of this research was to evaluate a mixed drink of UHT milk beverage with tamarillo fruit pulp, analyzing its antioxidant and physicochemical characteristics, by determining the content of ascorbic acid, phenolic compounds, carotenoids and their stability during refrigeration. The antioxidant capacity was studied through the DPPH method, ascorbic acid and carotenoids were determined by high performance liquid chromatography and the Folin-Ciocalteu method was used to analyze total phenols in the beverage. We found that the mixed beverage presented bioactive compounds recognized for their functional properties. A significant decrease in the content of bioactive compounds was observed during the first two weeks of refrigerated storage. There was a decrease in the total phenolic content of 33.150±2.020 to 21.467±1.360mg gallic acid equivalents (GAE)/100mL, as in the ascorbic acid content of 12.967±0.603 to 5.167±0.321mg/100mL and the β-carotene content from 243.00±5.66 to 146.50±2.12µg/100mL, which was reflected in the decrease of the antioxidant capacity of the beverage in a range of 3.450±0.041 to 1.581±0.025 Trolox mmol/L during the storage period at 4°C. The pH and total soluble solids remained constant, while the acidity increased significantly during the first week of storage.